2014
DOI: 10.1104/pp.114.240036
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Hormones and Their Stereoisomers Signal through Two Related Receptor Proteins to Induce Different Physiological Responses in Arabidopsis  

Abstract: Two a/b-fold hydrolases, KARRIKIN INSENSITIVE2 (KAI2) and Arabidopsis thaliana DWARF14 (AtD14), are necessary for responses to karrikins (KARs) and strigolactones (SLs) in Arabidopsis (Arabidopsis thaliana). Although KAI2 mediates responses to KARs and some SL analogs, AtD14 mediates SL but not KAR responses. To further determine the specificity of these proteins, we assessed the ability of naturally occurring deoxystrigolactones to inhibit Arabidopsis hypocotyl elongation, regulate seedling gene expression, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
322
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(345 citation statements)
references
References 51 publications
22
322
1
Order By: Relevance
“…Two of the four possible stereoisomers, designated GR24 5DS and GR24 4DO , have the same 2′R-configuration of the D-ring as found in all physiological SLs. These two isomers, and particularly GR24 5DS , are more active in D14-dependent bioassays than the other two isomers [31]. The same two isomers were selectively capable of stimulating the interaction between D14 and D3, with GR24 5DS being more potent than GR24 4DO ( Figure 5C), thus closely mimicking the effects of GR24 isomers in plants [31].…”
Section: Binding Of Gr24 Inside Of the D14 Lbp Is Required For The Inmentioning
confidence: 82%
See 1 more Smart Citation
“…Two of the four possible stereoisomers, designated GR24 5DS and GR24 4DO , have the same 2′R-configuration of the D-ring as found in all physiological SLs. These two isomers, and particularly GR24 5DS , are more active in D14-dependent bioassays than the other two isomers [31]. The same two isomers were selectively capable of stimulating the interaction between D14 and D3, with GR24 5DS being more potent than GR24 4DO ( Figure 5C), thus closely mimicking the effects of GR24 isomers in plants [31].…”
Section: Binding Of Gr24 Inside Of the D14 Lbp Is Required For The Inmentioning
confidence: 82%
“…These two isomers, and particularly GR24 5DS , are more active in D14-dependent bioassays than the other two isomers [31]. The same two isomers were selectively capable of stimulating the interaction between D14 and D3, with GR24 5DS being more potent than GR24 4DO ( Figure 5C), thus closely mimicking the effects of GR24 isomers in plants [31]. The activity to stimulate the D14-D3 interaction further correlates with the energetically most favorable binding conformation as judged by computational docking (Supplementary information, Figure S7A), and the docking position of the 5DS isomer is most consistent with the GR24 model (Supplementary information, Figure S7B).…”
Section: Binding Of Gr24 Inside Of the D14 Lbp Is Required For The Inmentioning
confidence: 99%
“…A study on the impact of stereochemical configuration on biological activities demonstrated that natural SLs -with 2'C atom in R configuration -inhibit hypocotyl elongation in Arabidopsis, preferentially through the D14-MAX2 signalling pathway, while the effects of karrikins and ent-GR24 (2'C atom in S configuration) on hypocotyl elongation and their induction of germination in dormant Arabidopsis seeds are mediated by the KAI2-MAX2 pathway (Scaffidi et al, 2014). To explore whether rac-N-PL exerts karrikin-like function in regulating seedling development, we examined the effect of two different concentrations (1 µM and 5 µM) of this compound on hypocotyl length.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…2). Importantly, kai2 mutants retain the ability to respond to exogenous strigolactones, and d14 mutants to karrikins (Waters et al 2012a;Scaffidi et al 2014). By extension, some max2 phenotypes are thus strigolactone related (as mediated by D14), and others are strigolactoneindependent (as mediated by KAI2).…”
Section: : Kai2/htl and D14mentioning
confidence: 97%